3D printing of abdominal immobilization masks for therapeutics: dosimetric, mechanical and financial analysis - Duarte, Jessica (2022)
Molding immobilization masks is a time-consuming process, strongly dependent on the healthcare professional, and potentially uncomfortable for the patient. Thus, an alternative sustainable automated production process is proposed for abdominal masks, using fused deposition modelling (FDM) 3D printing with polylactic acid (PLA). Radiological properties of PLA were evaluated by submitting a set of PLA plates to photon beam radiation, while estimations of their mechanical characteristics were assessed through numerical simulation. Based on the obtained results, the abdominal mask was 3D printed and process costs and times were analyzed. The plates revealed dose transmissions similar to the conventional mask at all energies, and mechanical deformation guarantees the required immobilization, with a 66% final cost reduction. PLA proved to be an excellent material for this purpose. Despite the increase in labour costs, a significant reduction in material costs is observed with the proposed process. However, the time results are not favorable, mainly due to the printing technique used in this study.